Death by caramel macchiato - Erickson, Alex (Erickson, Alex. Bookstore café mystery., 2024)
"When Pine Hills, Ohio, hosts an inter-town murder mystery game, bookstore-café owner and sometimes-sleuth Krissy Hancock assumes it'll all be in good fun, but that's before the competition claims its first real-life victim... The unique weekend-long event--a combination of a live-action role playing game and a theatrical production--draws competitors from all the neighboring towns, including Pine Hills' own Krissy and Rita. Although the actors, clues, and performances are spread across the community, somehow Krissy's team lands at the one location with an actual body... Police immediately call off the competition while they conduct a real murder investigation, but soon it's clear some folks are playing by their own set of rules. So it's up to Krissy and her pals to shuffle through the suspects and draw out the real killer before another player takes their final turn"--